Analisis Psikoakustik Gending Tari Topeng Gunungsari - Candra Kurniawan; Nurida Finahari; Gatot Soebiyakto (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2022)
Dance performances are art communication between dancers and their audience. The regional art unique characteristics are local cultural wealth form. One of the Malang regency traditional dance is the Gunungsari Mask dance. The dancer response to accompaniment gending can be analyzed from the psychoacoustic aspect. This study aims to analyze the psychoacoustic of the Gunungsari gending. Sound analysis was performed using Wave Surfer to obtain temporal and spectral signals. The WavePad application is used to get the FFT for spectral and TFT for temporal. Furthermore, Audacity is used to numerize the voice signal. Each sample was taken as 100 data from the graph per minute. The numerical results were processed using Microsoft Excel to obtain the graph trend line equation. The results showed that the Gunungsari gending had polynomial patterns for spectral and temporal. The temporal pattern corresponds to 6 degree polynomial regression while the spectral is of 3-4 degree. Thus, Gending Gunungsari has Angka Gending (as cited reference) that are in accordance and can be used as therapeutic gending.